Modification of Rabbit Yarn by Milk Protein Grafting and Cross-Linking. Issue 4 (December 2015) - Jiali, Li; Tonghua, Zhang; Lan, Cheng; Min, Guo
Rabbit yarn was treated by milk protein grafting and cross-linking to improve its abrasion resistance performance and breaking strength. Grafting ratio and washing fastness of the rabbit yarn after graft modification were tested. The surface morphology of the rabbit yarn before and after graft modification was observed by a scanning electron microscope(SEM). The mechanical properties and friction performances of the treated and untreated rabbit yarns were also tested. The treated yarns were utilized to design and weave rabbit hair-knitted fabric. The anti-pilling resistance of the rabbit hair-knitted fabric was tested by circular locus method; the pills were then counted and weighed. The stiffness of the fabric was observed. Results showed that milk protein could obviously be grafted on the fiber surface, resulting in a rougher surface of the treated fabric than that of the untreated ones. The average grafting ratio is 3.701%. The protein retention ratio of the rabbit yarn treated by milk protein grafting and cross-linking is 99.312%. The breaking strength of the rabbit yarn was enhanced and friction performance improved significantly after treatment. The pilling grade of the fabric significantly improved and the stiffness of the fabric was reduced.